The Role of Smart Economy in Developing Smart Cities - Youssef, Abdelrahman Taha; Hájek, Petr (IEEE (Institute of Electrical and Electronics Engineers), 2021)
Smart cities are often linked to development projects to achieve the level of smartness that city governments aspire to. There are several studies looking at how to evaluate smart city performance using different methodologies and evaluation criteria. Although there is no standard method on how to perform such an evaluation, we have observed that the Smart Economy is the most dominant dimension in evaluating smart cities. Of the 30 studies we analyzed between 2015 and 2020, smart economy was cited in 25 of them as a key dimension in evaluating smart cities. Therefore, in this paper we highlight the role of the Smart Economy dimension in smart city development and show how it is measured and evaluated in different assessment tools. In this article, we look in more detail at smart economy-related indicators used in different assessment tools. We draw on a theoretical approach with a combination of quantitative and qualitative analysis to explore commonalities and correlations among the top performing cities in the smart economy.
Úloha chytré ekonomiky v rozvoji chytrých měst
Keywords: smart economy; smart city